Implementation of Learning with the Problem Posing Method to Increase Activeness and Learning Outcomes of Physics in the Material of Temperature and Heat - Purnomo, M.; Aimran, Wan Mohm; Prasitpong, Singha (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to find out how physics learning using the Problem posing Method is implemented in high school and to find out whether learning physics using the Problem posing Method can increase the activeness and learning outcomes of high school students in physics. Methodology: This type of research is classroom action research carried out in 2 cycles. This research was conducted in high school. The subjects of this research were 31 students of class X high school. The research data is in the form of student activity and learning outcomes. Students' learning activity is known from the results of observation sheets, while students' learning outcomes are known from the results of evaluations carried out at the end of each cycle. Main Findings: The results showed that the active learning of students in cycle II showed an increase when compared to cycle I. The results showed learning with the Problem Posing model was preferred by students so that it was hoped that the teacher could apply the Problem Posing model as a variation in learning Physics. The limitation of the research which only applies the Problem Posing model to the material Temperature and Heat with a relatively short research time, it is hoped that further research can be carried out on other materials. Novelty/Originality of this study: The novelty of this research is that classroom action research was carried out to determine students' activeness in the learning process using a problem posing model specifically for learning physics on temperature and heat.